Pemanfaatan AR Sebagai Media Pembelajaran Pengenalan Jenis Tanaman Air Pelajaran IPA SMPN 13 Medan - Siti Sundari; khairunnisa; Dara Adistia Ayuna (Unit Pengelola Jurnal Universitas Harapan Medan, 2022)
Learning media is one of the methods used for success in the teaching and learning process. Utilization of learningmedia can be more effective with more interaction between teachers and students. The learning method for thestudents of SMP Negeri 13 Medan still uses learning media such as books and explanations from the teacher afterit is recorded by the students. Learning media is always evolving following existing technology, one of which isinteractive learning media using technology such as animation and audio-visual. The purpose of this study was todevelop learning media at SMP Negeri 13 Medan by making interactive learning media applications. Thisinteractive learning media uses Augmented Reality technology, Augmented reality is a technology that combinestwo-dimensional and or three-dimensional virtual objects into a real three-dimensional environment and thenprojects these virtual objects in real time. The application development method uses the Multimedia DevelopmentLife Cycle (MDLC) method. MDLC is a method for designing and developing media applications that combineimages, sound, video, animation, and other media. The results of the research based on the questionnaire weregiven to students who had used interactive media applications by giving opinions about the applications used.